Product configuration using redundancy and standardisation in an uncertain environment. Issue 21 (2nd November 2021) - Song, Qinyu; Ni, Yaodong; Ralescu, Dan A.
Abstract : Product configuration involves selecting common components/modules of individualised products. This is done according to customer requirements under mass customisation. However, the strategies adopted by most existing product configurators are often extreme, with either total diversity (mass personalisation) or standardised products (a limited set of products). In order to investigate the intermediate case in this situation, a new uncertain decision model is proposed in this paper. The aim is to find the optimal product configuration using a redundancy and standardisation strategy that minimises the total costs. In this model, customer requirements are defined and assembly sequences are initially constructed. Then, a manufacturing approach of modular multi-platform assembly is employed to increase uniqueness in mass customisation. Next, the uncertain decision model for product configuration is linearised and solved by uncertainty theory using CPLEX 12.8. Finally, a sensitivity analysis is conducted to suggest optimal platform number and producing strategies and determine the final customised product specification. From a case study of the mobile phone, we found that standardisation performs better than the redundancy strategy and a flexible platform strategy effectively reduces production costs.